Characteristics of Risk and Return in Risk Arbitrage - Mitchell, Mark; Pulvino, Todd (Journal of Finance, 2001)
ABSTRACT This paper analyzes 4,750 mergers from 1963 to 1998 to characterize the risk and return in risk arbitrage. Results indicate that risk arbitrage returns are positively correlated with market returns in severely depreciating markets but uncorrelated with market returns in flat and appreciating markets. This suggests that returns to risk arbitrage are similar to those obtained from selling uncovered index put options. Using a contingent claims analysis that controls for the nonlinear relationship with market returns, and after controlling for transaction costs, we find that risk arbitrage generates excess returns of four percent per year.